Answers

2016-03-25T21:14:18+05:30
Let man's age be x
his son's be y

according to given condition
x=y+24..........eq i

according to second condition
(x-12)=5(y-12)
x-12= 5y-60
x-12+60=5y
x+48=5y

now from eq i
(y+24)+48=5y
y+24+48=5y
24+48=5y-y
72=4y
y=18
x=y+24
x=18+24=42
0
2016-03-26T09:35:32+05:30
Let the present age of the son be 'x'

So, his father age = x + 24


12 yrs ago,
Son's age = x - 12
Fathers age = (x + 24) - 12
= x + 12

Given,
5(x -12) = x + 12
5x - 60 = x + 12
4x = 72
x = 72/4 = 18


So, the son's present age = 18 yrs

And, fathers present age = 18 + 24 = 42 yrs
1 5 1
X - Son's current age X +24 = father's current age X + 24 - 12= 5( X -12) X + 12 = 5X - 60 4X = 72 X = 18 / Son's age 18 + 24 = 42 / father's age